Synthesis and Study of Nanostructure Fe2o3 Film by Laser Assisted Spray Pyrolysis. - Chiad, Bahaa T; Sadik, Zainab S; Mahdi, Dunia K; Mohammed, Fatin H (Al-Nahrain Journal of Science, 2018)
Films of hematite (α-Fe2O3) were deposited by using laser assisted spray pyrolysis technique (LASP). The films were deposited on heated substrates with temperature 400̊C, once with using laser and other without laser, Structural analysis, using X-ray diffraction, verified the phase of the films and revealed that the films had a polycrystalline structure composed of nano-crystallites. Atomic force microscopy indicated that the films which deposited by laser assisted had smooth surface with smallest lateral grain size compared with the films deposited without laser, where the average grain size for the film deposited without laser about 146nm,while the average grain size for the film deposited with laser about 77nm.